Impact of digital village development on farmers’ human settlement environment improvement behaviors - Guodong Zhao; Hongwu Sun (Frontiers in Sustainable Food Systems)
IntroductionAs digital village construction advances, digital technologies are gradually permeating various aspects of rural life, providing a new avenue for improving rural human settlement environment (RHSE).MethodsWe matched the 2020 and 2021 data from the China Land Economic Survey (CLES) with the County Digital Rural Index (CDRI), exploring how digital village development (DVD) influences farmers’ human settlement environment improvement behaviors (HSEIBs).Results and discussionResearch findings indicate that DVD has significantly increased farmers’ probability of disposing of domestic wastewater scientifically and adopting sanitation toilets, with robustness checks conducted. Further analysis reveals that this positive impact is primarily realized through effects of enriching villages, enriching villagers and social interaction. The analysis of heterogeneity reveals that in households with a higher proportion of seniors, DVD significantly raises the usage of sanitation toilets but does not significantly promote the scientific treatment of domestic wastewater. Additionally, when we subdivide DVD into different dimensions, we find that the digitalization of rural infrastructure, rural economy, rural life and rural governance can effectively facilitate farmers’ HSEIBs, but the digitalization of rural governance has the least impact. Our findings not only enrich the field of digital well-being research but also shed light on the digital divide problem in rural China.